2019
DOI: 10.1016/j.cmet.2019.02.008
|View full text |Cite
|
Sign up to set email alerts
|

A New Transkingdom Dimension to NO Signaling

Abstract: Bacterial-derived metabolites profoundly influence the host's cellular and organismal physiology. Seth et al. (2019) report that via interspecies S-nitrosylation, microbiota-derived nitric oxide directly alters the host's Argonaute family protein activity, and consequently impinges on the overall post-transcriptional gene silencing program through the microRNA (miRNA) machinery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…OPN predominantly heightens inflammatory responses and disrupts glucose homeostasis in adipocytes and hepatocytes, which may further impair phosphatidylcholine and cholesterol metabolism and thus exacerbate nonalcoholic cirrhosis of the liver [ 64 , 70 ]. However, other studies showed that OPN can safeguard β-cells by lowering the production of iNOS and maintaining Ca 2+ homeostasis [ 71 ]. Studies have long shown that energy metabolism is regulated by OPN released by adipocytes, hepatocytes, and macrophages.…”
Section: Bone Cells and Global Energy Metabolismmentioning
confidence: 99%
“…OPN predominantly heightens inflammatory responses and disrupts glucose homeostasis in adipocytes and hepatocytes, which may further impair phosphatidylcholine and cholesterol metabolism and thus exacerbate nonalcoholic cirrhosis of the liver [ 64 , 70 ]. However, other studies showed that OPN can safeguard β-cells by lowering the production of iNOS and maintaining Ca 2+ homeostasis [ 71 ]. Studies have long shown that energy metabolism is regulated by OPN released by adipocytes, hepatocytes, and macrophages.…”
Section: Bone Cells and Global Energy Metabolismmentioning
confidence: 99%